Peluang Integrasi Gizi Seimbang dalam Proses Pembelajaran di SD Plus Rahmat Kediri - Yayuk Farida Baliwati; Akifa Laila Rusyda; Cesilia Meti Dwiriani; Siti Amanah; Resa Ana Dina; Veny Rachmalinda; Jihan Alfira; Prita Dhyani Swamilaksita (Institut Pertanian Bogor, 2025)
The nutritional status of school children currently still experiences very complex disparities, including severely thin, underweight, overweight, and obesity. The government's initiatives against nutritional problems in school-aged children include, among other things, the delivery of school-based balanced nutritional guidelines. The present activity aims to identify the opportunity for balanced nutritional guideline integration through the learning process in the Merdeka Curriculum at SD Plus Rahmat, Kediri City. This study used mixed methods and a sequential explanatory design through qualitative and quantitative (descriptive) analyses. The activity was carried out from April 20‒May 30, 2024, and was the initial stage of the 2024 Dosen Pulang Kampung multi-activities. The implementation method consisted of observation and focus group discussions (FGD). The subjects were 15 participants, including teachers and Yayasan Taman Pendidikan Rahmat stakeholders. The findings show that six out of seven P5 program contents have been integrated into literacy competency of nutrition, such as the types and functions of food and nutrition. Most FGD participants (±90%) had moderate to high average nutritional knowledge and behavior, namely 75.6 and 84.7, respectively. The results also show that the co-curricular program, namely the Project for Strengthening the Profile of Pancasila Students (P5), is an opportunity for PGS integration. Integrating PGS into literacy and numeracy in P5 still requires ongoing teacher assistance. The assistance is expected to increase teachers' understanding and behavior towards balanced nutritional guidelines, conveying how to shape student character according to balanced nutritional guidelines.implemented with school children to shape the character regarding the Balanced Nutrition Guidelines.